Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
Anh Bùi Thị
Xem chi tiết
Nguyễn An
Xem chi tiết
Nguyễn Việt Lâm
13 tháng 8 2021 lúc 1:19

Đặt \(P=\dfrac{a^3}{a^2+b^2+ab}+\dfrac{b^3}{b^2+c^2+bc}+\dfrac{c^3}{c^2+a^2+ca}\)

Ta có: \(\dfrac{a^3}{a^2+b^2+ab}=a-\dfrac{ab\left(a+b\right)}{a^2+b^2+ab}\ge a-\dfrac{ab\left(a+b\right)}{3\sqrt[3]{a^3b^3}}=a-\dfrac{a+b}{3}=\dfrac{2a-b}{3}\)

Tương tự: \(\dfrac{b^3}{b^2+c^2+bc}\ge\dfrac{2b-c}{3}\) ; \(\dfrac{c^3}{c^2+a^2+ca}\ge\dfrac{2c-a}{3}\)

Cộng vế:

\(P\ge\dfrac{a+b+c}{3}=673\)

Dấu "=" xảy ra khi \(a=b=c=673\)

Phạm Hải Nam
Xem chi tiết
Triệu Thị Diễm Hằng
22 tháng 4 2022 lúc 15:32

ké ý (b) ạ!!!

Phạm Hải Nam
Xem chi tiết
Hoàng Hưng Đạo
Xem chi tiết
zanggshangg
14 tháng 5 2021 lúc 21:04

a )

`VP= (a+b)^3-3ab(a+b)`

     `=a^3+3a^2b+3ab^2+b^3-3a^2b-3ab^2`

     `=a^3+b^3 =VT (đpcm)`

b) 

b) Ta có

`VT=a3+b3+c3−3abc`

     `=(a+b)3−3ab(a+b)+c3−3abc`

     `=[(a+b)3+c3]−3ab(a+b+c)`

     `=(a+b+c)[(a+b)2+c2−c(a+b)]−3ab(a+b+c)`

     `=(a+b+c)(a2+b2+2ab+c2−ac−bc−3ab)`

    `=(a+b+c)(a2+b2+c2−ab−bc−ca)=VP`

  
zanggshangg
14 tháng 5 2021 lúc 21:09

 

a) Ta có:

`VP= (a+b)^3-3ab(a+b)`

     `=a^3 + b^3+3ab ( a + b )- 3ab ( a + b )`

     `=a^3 + b^3=VT(dpcm)`

b) Ta có

`VT=a^3+b^3+c^3−3abc`

     `=(a+b)^3−3ab(a+b)+c^3−3abc`

     `=[(a+b)^3+c^3]−3ab(a+b+c)`

     `=(a+b+c)[(a+b)^2+c^2−c(a+b)]−3ab(a+b+c)`

     `=(a+b+c)(a^2+b^2+2ab+c^2−ac−bc−3ab)`

    `=(a+b+c)(a^2+b^2+c^2−ab−bc−ca)=VP`

Nguyên Lê
Xem chi tiết
Wheatley
Xem chi tiết
Trần Nhật Huy
23 tháng 6 2023 lúc 10:53

loading...

minh bùi
Xem chi tiết
Trên con đường thành côn...
13 tháng 7 2023 lúc 20:28

\(a\left(b^2+c^2\right)+b\left(a^2+c^2\right)+c\left(a^2+b^2\right)-2abc-a^3-b^3-c^3\)

\(=c\left(a-b\right)^2+\left[ab^2+ac^2+a^2b+bc^2-a^3-b^3-c^3\right]\)

\(=c\left(a-b\right)^2+c^2\left(a+b-c\right)+ab^2+a^2b-a^3-b^3\)

\(=c\left(a-b\right)^2+c^2\left(a+b-c\right)-\left(a^3-a^2b\right)+\left(ab^2-b^3\right)\)

\(=c\left(a-b\right)^2+c^2\left(a+b-c\right)-a^2\left(a-b\right)+b^2\left(a-b\right)\)

\(=c\left(a-b\right)^2+c^2\left(a+b-c\right)-\left(a+b\right)\left(a-b\right)^2\)

\(=-\left(a-b\right)^2\left(a+b-c\right)+c^2\left(a+b-c\right)\)

\(=\left(a+b-c\right)\left(a-b+c\right)\left(-a+b+c\right)\)

Kwalla
Xem chi tiết
Nguyễn Lê Phước Thịnh
27 tháng 11 2023 lúc 8:29

\(\left(a+b+c\right)^2=a^2+b^2+c^2\)

=>\(a^2+b^2+c^2+2\left(ab+bc+ac\right)=a^2+b^2+c^2\)

=>\(2\left(ab+bc+ac\right)=0\)

=>ab+bc+ac=0

\(\dfrac{1}{a^3}+\dfrac{1}{b^3}+\dfrac{1}{c^3}=\dfrac{3}{abc}\)

=>\(\dfrac{\left(bc\right)^3+\left(ac\right)^3+\left(ab\right)^3}{\left(abc\right)^3}=\dfrac{3}{abc}\)

=>\(\left(bc\right)^3+\left(ac\right)^3+\left(ab\right)^3=3\left(abc\right)^2\)

\(\Leftrightarrow\left(ab+bc\right)^3-3\cdot ab\cdot bc\cdot\left(ab+bc\right)+\left(ac\right)^3=3\left(abc\right)^2\)

=>\(\left(-ac\right)^3-3\cdot ab\cdot bc\cdot\left(-ac\right)+\left(ac\right)^3-3\left(abc\right)^2=0\)

=>\(-a^3c^3+a^3c^3+3a^2b^2c^2-3a^2b^2c^2=0\)

=>0=0(đúng)